2001
DOI: 10.1016/s0006-3495(01)75725-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Capsid Protein Forms Spherical (Immature-Like) and Tubular (Mature-Like) Particles in Vitro: Structure Switching by pH-induced Conformational Changes

Abstract: The viral genome and replicative enzymes of the human immunodeficiency virus are encased in a shell consisting of assembled mature capsid protein (CA). The core shell is a stable, effective protective barrier, but is also poised for dissolution on cue to allow transmission of the viral genome into its new host. In this study, static light scattering (SLS) and dynamic light scattering (DLS) were used to examine the entire range of the CA protein response to an environmental cue (pH). The CA protein assembled tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 37 publications
7
72
0
Order By: Relevance
“…52 Nuclear magnetic resonance Solid state NMR experiments on both uniformly 15 N, 13 C-labeled and 1,3-13 C 2 -glycerol-labeled CA assemblies were performed with a Varian InfinityPlus spectrometer operating at 150.7 MHz 13 C NMR frequency and a Varian triple-channel balun MAS NMR probe with 3.2 mm rotors. Sample heating by rf irradiation was significant, due to the 1M NaCl concentration in CA assembly samples, requiring that cooling gas at À80 C be supplied to the variable-temperature stack of the NMR probe to maintain sample temperatures in the [30][31][32][33][34][35][36][37][38][39][40] C range. The temperature of the sample was higher than that of the cooling gas both because the cooling gas warmed by $50 C while passing through the variable-temperature stack and because the rf irradiation heated the sample directly during measurements.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…52 Nuclear magnetic resonance Solid state NMR experiments on both uniformly 15 N, 13 C-labeled and 1,3-13 C 2 -glycerol-labeled CA assemblies were performed with a Varian InfinityPlus spectrometer operating at 150.7 MHz 13 C NMR frequency and a Varian triple-channel balun MAS NMR probe with 3.2 mm rotors. Sample heating by rf irradiation was significant, due to the 1M NaCl concentration in CA assembly samples, requiring that cooling gas at À80 C be supplied to the variable-temperature stack of the NMR probe to maintain sample temperatures in the [30][31][32][33][34][35][36][37][38][39][40] C range. The temperature of the sample was higher than that of the cooling gas both because the cooling gas warmed by $50 C while passing through the variable-temperature stack and because the rf irradiation heated the sample directly during measurements.…”
Section: Electron Microscopymentioning
confidence: 99%
“…1 The capsid is believed to be formed by a triangular lattice of CA hexamers, with 12 CA pentamers unevenly distributed at the two ends of the cone to produce a closed shell. 2 Although much progress has been made toward understanding the structure, stability, and assembly of the HIV-1 capsid, through electron microscopy, [3][4][5][6][7][8][9][10] X-ray crystallography, [11][12][13][14][15][16][17][18][19][20] solution nuclear magnetic resonance (NMR), 13,[21][22][23][24][25][26][27] and various biophysical techniques, [28][29][30][31][32][33][34][35][36][37][38][39][40] substantial questions remain regarding the details of intermolecular interactions within and between CA hexamers, the structural variations that permit CA to form both hexamers and pentamers, the driving force for curvature and closure of the CA lattice, and the mechanism and pathway for CA self-assembly. In principle, modern solid state NMR techniques, which can provide sitespecific molecular-level structural information about noncrystalline protein assemblies, [41][...…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence suggests that the morphology of the assembled structures may be influenced by pH (12,21). Gag constructs with most of MA deleted assemble into spherical polymers at pH 8.0 and assemble into cylindrical polymers at pH 6.0 (21).…”
mentioning
confidence: 99%
“…Gag constructs with most of MA deleted assemble into spherical polymers at pH 8.0 and assemble into cylindrical polymers at pH 6.0 (21). However, modeling of light-scattering data suggested that CA assembled into cylindrical polymers at pH 7.0 and into spherical polymers at pH 6.8 (12). Similarly, the CA protein itself undergoes changes concomitant with a change in pH, where the radius of CA protein increased by ca.…”
mentioning
confidence: 99%
“…In [3], it is demonstrated that HIV-1 VLPs could have a larger cone angle resulting in a (4,8)-cone shape. Mathematically, there are five possible cones: (5,7), (4,8), (3,9), (2,10), (1,11). However, extreme distributions such as the (2,10)-and (1,11)-cones are rarely seen in the nature [15].…”
Section: Curvature Concentrations On the Hiv-1 Conical Capsidmentioning
confidence: 99%